Effect of quality, porosity and density on the compression properties of cork (Holz als Roh- und Werkstoff, 2008)
The compression properties of cork were studied on samples obtained from cork planks of two commercial quality classes (good and poor quality), with densities ranging from 0.12–0.20g cm−3 and porosities from 0.5 to 22.0%. The stress-strain curves were characterized by an elastic region up to approximately 5% strain, followed by a large plateau up to 60% strain caused by the progressive buckling of cell walls, and a steep stress increase for higher strains corresponding to cell collapse. The direction of compression was a highly signiﬁcant factor of variation, with cork showing higher strength for the radial compression. Density inﬂuenced compression and cork samples with higher density showed overall larger resistance to compression in the three directions. In the elastic region, an exponential model of Young’s modulus in function of cork density could be adjusted. The effect of porosity on compression was small and the stress-strain curves were similar regardless of the porosity of the samples, although there was a trend toward an overall increase of stress with porosity for higher strains. Porosity was characterised by a high variability in the anatomical features of the lenticular ﬁlling material and the presence of collapsed and thick walled ligniﬁed cells. The inclusion of a porosity parameter for the modelling of the elastic modulus did not improve the prediction obtained with densitybased models. There was no signiﬁcant difference in the compression properties of cork samples obtained from cork planks of good and poor quality classes.

THE CELLULAR STRUCTURE OF CORK FROM QUERCUS SUBER L (IAWA Bulletin, 1987)
The main characteristics of the cellular struc- ture of cork from Quercus suber L. are review- ed and comph;mented with new observations of virgin and reproduction cork by scanning electron microscopy. Particular emphasis is given to cell geometry and topology and to the corrugations that are observed in the cell walls. The effect of the growth season in these fea- tures is described. Large variations in cell size, wall thickness ajld corrugations are reported. Key words: Quercus SIlber, cork, cell gcometry, topology, cell wall corrugations.